Block polyethylene and preparation method thereof

By adding specific metal complexes and cocatalysts to the reaction system of polyolefin materials and using ethylene as the only monomer, block polyethylene is prepared, which solves the problems of insufficient material toughness and poor blending uniformity, and significantly improves the performance of the material.

CN119899295AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311408217.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

In the prior art, the toughness of the polyolefin material is insufficient and the blending uniformity is poor, which affects the application performance of the material.

Method used

By adding α-diimine nickel metal complex, metallocene complex, cocatalyst, alkyl zinc chain shuttle agent and organic solvent to the reaction system, ethylene solution polymerization was performed using ethylene as the only polymerization monomer to prepare block polyethylene with branching and crystallinity.

Benefits of technology

The blend on the molecular level is realized, the problem of poor blending uniformity is solved, and the processing and mechanical properties of polyethylene materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004517284640000041
    Figure BDA0004517284640000041
  • Figure BDA0004517284640000051
    Figure BDA0004517284640000051
  • Figure BDA0004517284640000061
    Figure BDA0004517284640000061
Patent Text Reader

Abstract

The invention relates to block polyethylene and a preparation method thereof, and the preparation method comprises the step of carrying out ethylene solution polymerization in a reaction system added with an alpha-diimine nickel metal complex, a metallocene complex, a promoter, an alkyl zinc chain shuttling agent and an organic solvent by using ethylene as a unique polymerization monomer. The preparation method is simple and easy to operate, industrial production is easy to realize, and the obtained block polyethylene has more excellent mechanical properties and processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of olefin polymerization, and in particular to a block polyethylene and a preparation method thereof. Prior art

[0002] Polyolefin materials are widely used in industrial packaging materials, agricultural films, medical and health packaging materials, food packaging materials, urban pipelines and other aspects of daily life due to their good mechanical properties, excellent processing properties, strong chemical corrosion resistance, and good electrical insulation properties. They have become the polymer material with the largest output and the widest application among the three major synthetic resins in the world. Ethylene is the simplest, cheapest and most readily available olefin monomer. If polyethylene materials with different application properties can be prepared only from ethylene monomer, it will be of great significance and is also one of the hot research topics in academia and industry.

[0003] Usually, the homopolymerization of ethylene using metallocene catalysts produces linear polyethylene, which has high crystallinity, high melting point and high tensile strength, but relatively poor toughness. In order to improve the toughness of polyethylene materials, ethylene is generally copolymerized with other α-olefin monomers, such as propylene, 1-butene, 1-hexene and 1-octene, to prepare linear low-density polyethylene with certain branches. Brookhart and Grubbs et al. found that the homopolymerization of ethylene using late transition metal (nickel or palladium) catalysts can produce hyperbranched polyethylene with rich branched structures (J. Am. Chem. Soc., 1995, 117 (23): 6414-6415; Organometallics. 1998, 17: 3149-3151). Hyperbranched polyethylene has good solubility, low solution and melt viscosity, and good toughness. It can be used as a plastic toughening modifier and blended with high-density polyethylene or polypropylene to improve its toughness. However, in actual use, it is found that there are problems such as difficulty in blending uniformity and poor compatibility, which have an adverse effect on the use of the material. As is well known in the art, block polymers have better mechanical properties and processing properties than physical blends. Block polymers contain both "soft segments" formed by branched polyethylene and "hard segments" formed by linear polyethylene on their molecular chains, which can be considered as blends at the molecular level, effectively solving the problem of blending uniformity.

[0004] The existing method for preparing block polyethylene is usually the block copolymerization of ethylene and alpha-olefin. Dow Corporation of the United States adopts a novel non-metallocene catalyst combination to invent a brand-new olefin chain shuttle polymerization technology (Chain ShuttlingPolymerization), and has launched a brand-new polyolefin thermoplastic elastomer-ethylene octene block copolymer (Olefin Block Copolymer, referred to as OBC). OBC is composed of a crystallizable polyethylene hard segment with extremely low comonomer content and high melting point and an amorphous polyethylene soft segment with high comonomer content and low glass transition temperature. Compared with POE, OBC has a higher crystallization temperature and melting point, a more regular crystalline form, and a lower glass transition temperature, and all shows more superior performance in terms of tensile strength, elongation at break and elastic recovery. (Science, 2006, 312: 714-719). However, due to the expensive 1-octene monomer used during synthesis, its production cost is higher, which is not conducive to promotion and practical application. Summary of the invention

[0005] The purpose of the present application is to provide a block polyethylene and a preparation method thereof, wherein the block polyethylene forms a blend of crystalline polyethylene segments and amorphous polyethylene segments at the molecular level, effectively overcoming the problems of uneven mixing and poor compatibility of the intermolecular blend, and has more excellent processing performance and mechanical properties.

[0006] In order to achieve the above-mentioned purpose, on the one hand, the present application provides a method for preparing block polyethylene, comprising the steps of carrying out ethylene solution polymerization using ethylene as the only polymerization monomer in a reaction system added with an α-diimine nickel metal complex, a metallocene complex, a co-catalyst, an alkyl zinc chain shuttling agent and an organic solvent, wherein the co-catalyst is selected from at least one of alkyl aluminum, alkyl aluminoxane, halogenated alkyl aluminum, aryl borane and aryl borate.

[0007] On the other hand, the present application provides a block polyethylene having a weight average molecular weight of 5-1 million g / mol, a polymer dispersibility index (PDI) of 1.5-4.0, a branching degree of 20-75 / 1000C, and a crystallinity of 5-35%.

[0008] Preferably, the block polyethylene is prepared by the block polyethylene preparation method of the present application.

[0009] Compared with the prior art, the preparation method of the present application uses only ethylene as the only polymerization monomer, and does not need to use expensive α-olefins as comonomers, so as to obtain block polyethylene having both "soft segments" formed by branched polyethylene and "hard segments" formed by linear polyethylene, forming a blend at the molecular level, effectively solving the problems of difficult mixing and poor compatibility of intermolecular blends in the prior art, and the provided block polyethylene has better processing performance and mechanical properties than physical blends. In the method of the present application, the α-diimine nickel metal complex and metallocene complex used have high high temperature thermal stability, so the composite catalyst provided can catalyze the polymerization of ethylene in an organic solvent at a relatively high temperature (≥60°C), and has high polymerization activity (greater than 10 6 gPE / (molcat·h)), the molecular weight is easy to control, and the method of the present invention is simple and easy to operate, does not require harsh reaction conditions, and is easy to realize industrial production. DETAILED DESCRIPTION

[0010] The specific implementation methods of the present application are described in detail below, but it should be noted that the protection scope of the present application is not limited by these specific implementation methods, but is determined by the claims in the appendix.

[0011] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values ​​close to the exact value, such as all possible numerical values ​​within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values ​​of the range, the endpoint values ​​and the specific point values ​​in the range, and the specific point values ​​can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.

[0012] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.

[0013] In the context of this application, unless otherwise expressly defined or the meaning is beyond the comprehension of a person skilled in the art, hydrocarbon or hydrocarbon derivative groups having more than 3 carbon atoms (such as propyl, propoxy, butyl, butane, butene, butenyl, hexane, etc.) have the same meaning when not preceded by the prefix "n". For example, propyl is generally understood to be n-propyl, and butyl is generally understood to be n-butyl, unless otherwise expressly defined.

[0014] In this application, except for the contents clearly stated, any matters or items not mentioned are directly applicable to the aspects known in the art without any changes. Moreover, any embodiment described herein can be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of this application, and should not be regarded as new contents not disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.

[0015] All patent and non-patent literature, including but not limited to textbooks and journal articles, mentioned herein are incorporated herein by reference in their entirety.

[0016] As described above, in the first aspect, the present application provides a method for preparing block polyethylene, comprising the steps of carrying out ethylene solution polymerization using ethylene as the only polymerization monomer in a reaction system to which an α-diimine nickel metal complex, a metallocene complex, a co-catalyst, an alkyl zinc chain shuttling agent and an organic solvent are added, wherein the co-catalyst is selected from at least one of alkyl aluminum, alkyl aluminoxane, halogenated alkyl aluminum, aryl borane and aryl borate.

[0017] In a preferred embodiment, the α-diimine nickel metal complex (also referred to herein as catalyst A) is selected from one or more metal complexes represented by general formula (Ia) or (Ib):

[0018]

[0019] In formula (Ia) and (Ib), R1 and R2 are independently hydrogen, C1-C4 alkyl, C1-C4 haloalkyl, halogen or C1-C4 alkoxy; n is an integer from 0 to 4; R3, R4, R6 and R7 are independently C1-C6 chain alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl or C1-C4 alkyl substituted with phenyl; R5 and R8 are independently hydrogen, C1-C6 chain alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl, C1-C4 alkyl substituted with phenyl, halogen or C1-C4 alkoxy; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl, wherein the substituted phenyl has 1 to 5 substituents selected from the group consisting of halogen, C1-C4 alkyl and C1-C4 haloalkyl.

[0020] In a further preferred embodiment, as the catalyst A, for example, the following metal complexes can be cited as specific examples:

[0021]

[0022]

[0023] It should be noted that the above metal complexes can be used alone or mixed in any proportion.

[0024] In a further preferred embodiment, the α-diimine nickel metal complex (catalyst A) is selected from one or more complexes having the following chemical formula:

[0025]

[0026] In a preferred embodiment, the metallocene complex (also referred to herein as catalyst B) is selected from one or more of the metal complexes represented by general formula (II):

[0027]

[0028] In formula (II), R' is a C1-C8 straight or branched alkylene group, a C13-C21 diaryl alkylene group, a C2-C8 dialkylsilylene group or a C12-C20 diaryl silylene group, preferably a C1-C4 straight or branched alkylene group, a C13-C17 diaryl alkylene group, a C2-C4 dialkylsilylene group or a C12-C16 diarylsilylene group, more preferably a methylene group, an ethylene group, an isopropylidene group, a diphenylmethylene group, a dimethylsilylene group or a diphenylsilylene group; and Each independently represents an unsubstituted or substituted cyclopentadienyl, fluorenyl or indenyl; M is a Group IVB metal, preferably titanium or zirconium; and each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl.

[0029] In a preferred embodiment, the molar ratio of catalyst A to catalyst B added to the reaction system (calculated on the basis of the central metal atom) is 1:10 to 10:1, preferably 2:8 to 8:2, and more preferably 4:6 to 6:4.

[0030] In a preferred embodiment, the structural formula of the alkyl aluminum as a co-catalyst is as shown in formula (IIIa),

[0031] Al(R)3 (IIHa)

[0032] Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, more preferably selected from ethyl and isobutyl. In addition, the alkyl aluminum can be used alone or in any combination in any proportion.

[0033] Specifically, examples of the alkyl aluminum include trimethyl aluminum (Al(CH3)3), triethyl aluminum (Al(CH3CH2)3), tri-n-propyl aluminum (Al(n-C3H7)3), tri-isopropyl aluminum (Al(i-C3H7)3), tri-isobutyl aluminum (Al(i-C4H9)3), tri-n-pentyl aluminum (Al(n-C5H 11 )3) Tri-n-hexyl aluminum (Al(n-C6H 13 )3), diethylmethylaluminum (Al(CH3)(CH3CH2)2), and dimethylethylaluminum (Al(CH3)2(CH3CH2)), etc., among which trimethylaluminum, triethylaluminum, and triisobutylaluminum are preferred.

[0034] In a preferred embodiment, the general structural formula of the alkylaluminoxane used as a co-catalyst is as shown in formula (IIIb) or (IIIc),

[0035]

[0036] Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, more preferably selected from methyl and ethyl, and n is any integer in the range of 1-50, preferably any integer in the range of 10-30. In addition, the alkylaluminoxane can be used alone or in combination in any proportion.

[0037] Specifically, the alkylaluminoxane is preferably selected from methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, n-butylaluminoxane, modified methylaluminoxane and modified ethylaluminoxane, and more preferably methylaluminoxane and modified methylaluminoxane.

[0038] In a preferred embodiment, the structural formula of the alkyl aluminum halide as a co-catalyst is as shown in formula (IIId),

[0039] Al(R) n X 3-n (IIId)

[0040] Wherein, each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, more preferably selected from ethyl and isobutyl, X is halogen, preferably chlorine or bromine, and n is 1 or 2. In addition, the alkyl aluminum halide can be used alone or in combination in any proportion.

[0041] Specifically, as the halogenated alkyl aluminum, for example, there can be mentioned dimethylaluminum monochloride (Al(CH3)2Cl), dimethylaluminum dichloride (Al(CH3)Cl2), diethylaluminum monochloride (Al(CH3CH2)2Cl), diethylaluminum dichloride (Al(CH3CH2)Cl2), dipropylaluminum monochloride (Al(C3H7)2Cl), dipropylaluminum dichloride (Al(C3H7)Cl2), di-n-butylaluminum monochloride (Al(n-C4H9)2Cl), di-n-butylaluminum dichloride (Al(n-C4H9)Cl2), diisobutylaluminum monochloride (Al(i-C4H9)2Cl), diisobutylaluminum dichloride (Al(i-C4H9)Cl2), di-n-pentylaluminum monochloride (Al(n-C5H 11 )2Cl), dichloropentylaluminum (Al(n-C5H 11 )Cl2), diisopentylaluminum monochloride (Al(i-C5H 11 )2Cl), dichloroisopentylaluminum (Al(i-C5H 11 )Cl2), di-n-hexylaluminum chloride (Al(n-C6H 13 )2Cl), dichlorohexyl aluminum (Al(n-C6H 13 )Cl2), diisohexylaluminum monochloride (Al(i-C6H 13 )2Cl), dichloroisohexylaluminum (Al(i-C6H 13 )Cl2), chloromethyl ethylaluminum (Al(CH3)(CH3CH2)Cl), chloromethyl propylaluminum (Al(CH3)(C3H7)Cl), chloromethyl n-butylaluminum (Al(CH3)(n-C4H9)Cl), chloromethyl isobutylaluminum (Al(CH3)(i-C4H9)Cl), chloroethyl propylaluminum (Al(CH2CH3)(C3H7)Cl), chloroethyl n-butylaluminum (Al(CH2CH3)(n-C4H9)Cl), chloroethyl isobutylaluminum (Al(CH2CH3)(i-C4H9)Cl), etc., preferably selected from diethylaluminum chloride, ethylaluminum dichloride, di-n-butylaluminum chloride, n-butylaluminum dichloride, diisobutylaluminum chloride, di-n-hexylaluminum chloride and n-hexylaluminum dichloride, further preferably selected from diethylaluminum chloride and ethylaluminum dichloride.

[0042] In a preferred embodiment, the arylborane and arylborate as cocatalyst are selected from triphenylboron, tri(pentafluorophenyl)boron, triphenylcarbon tetra(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(pentafluorophenyl)borate, triethylammonium tetra(pentafluorophenyl)borate, 1-butyl-3-methylimidazole tetrafluoroborate, ferrocene tetrafluoroborate, trimethylammonium tetraphenylborate, triethylammonium tetraphenylborate, triisopropylammonium tetraphenylborate, tri-n-butylammonium tetraphenylborate, trimethylammonium tetra(4-methylphenyl)borate, triisopropylammonium tetra(4-methylphenyl)borate, ) borate, trimethylammonium tetrakis(2,4-dimethylphenyl)borate, triethylammonium tetrakis(2,4-dimethylphenyl)borate, trimethylammonium tetrakis(4-trifluoromethylphenyl)borate, tri-n-butylammonium tetrakis(4-trifluoromethylphenyl)borate, tri-n-butylammonium tetrakis(pentafluorophenyl)borate and N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, more preferably one or more selected from tris(pentafluorophenyl)boron, triphenylcarbon tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and triethylammonium tetrakis(pentafluorophenyl)borate.

[0043] In a preferred embodiment, the molar ratio of the total amount of the co-catalysts alkylaluminum, alkylaluminoxane and halogenated alkylaluminum added in the reaction system (calculated in terms of aluminum atoms) to the total amount of the catalyst A and the catalyst B (calculated in terms of central metal atoms) is (10-5000):1, preferably (100-2000):1, more preferably (500-1000):1; and / or the molar ratio of the total amount of the co-catalysts arylborane and aryl borate added in the reaction system (calculated in terms of boron atoms) to the total amount of the catalyst A and the catalyst B (calculated in terms of central metal atoms) is (1-10):1, preferably (2-5):1.

[0044] In a preferred embodiment, the alkyl zinc chain shuttling agent is selected from at least one of the organozinc compounds represented by the general structural formula (IV),

[0045] Zn(R)2(IV)

[0046] Wherein, each group R is independently selected from C1-C10 straight chain or branched alkyl, preferably selected from at least one of methyl, ethyl, isopropyl, n-butyl, isobutyl and n-hexyl, more preferably selected from at least one of methyl and ethyl.

[0047] In a preferred embodiment, the molar ratio of the amount of the alkyl zinc chain shuttling agent added to the reaction system (calculated as zinc atoms) to the total amount of the catalyst A and the catalyst B (calculated as central metal atoms) is (1-1000):1, preferably (50-600):1, and more preferably (100-500):1.

[0048] In a preferred embodiment, the organic solvent is selected from aromatic hydrocarbons, alkanes and halogenated alkanes, preferably selected from one or more of toluene, dichloromethane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane and Isopare series solvents, more preferably selected from one or more of n-pentane, n-hexane, cyclohexane, toluene and dichloromethane.

[0049] In a preferred embodiment, the polymerization reaction conditions include: a temperature of 0-150°C, preferably 60-100°C; and a polymerization pressure of 0.1-4.0 MPa, preferably 0.5-3.0 MPa.

[0050] In the method of the present application, the method of adding catalyst A, catalyst B, co-catalyst and chain shuttling agent to the polymerization reaction system is not particularly limited, and the co-catalyst may be added first, and then catalysts A, B and chain shuttling agent, or the co-catalyst and chain shuttling agent may be added first, and then catalysts A and B may be added, or the four may be contacted and mixed first and then added together, or added separately and simultaneously, or part of the co-catalyst may be added first, and then catalysts A, B, chain shuttling agent and remaining co-catalyst may be added simultaneously. When catalysts A, B, chain shuttling agent and co-catalyst are added separately, they may be added sequentially through the same feeding pipeline, or sequentially through multiple feeding pipelines, or simultaneously through multiple feeding pipelines.

[0051] In addition, in the method of the present application, the cocatalyst alkylaluminum, aluminoxane and alkylaluminum halide are generally used in the form of a solution. When preparing the solution of the cocatalyst, there is no particular limitation on the solvent used, as long as it can dissolve the cocatalyst. The solvent is generally selected as an alkane solvent, such as n-pentane, isopentane, cyclopentane, neopentane, etc., or an aromatic solvent, such as toluene, ethylbenzene, xylene, etc. According to the present application, in order to facilitate subsequent separation, it is preferred to use a solvent that is the same as the polymerization solvent; or a solvent that is the same as one of the solvents in the mixed solvent for polymerization.

[0052] In a second aspect, the present application provides a block polyethylene having a weight average molecular weight of 5-1 million g / mol, a polymer dispersibility index (PDI) of 1.5-4.0, a branching degree of 20-75 / 1000C, and a crystallinity of 5-35%.

[0053] In a preferred embodiment, the block polyethylene has a weight average molecular weight of 100,000-400,000 g / mol, a polymer dispersibility index (PDI) of 1.6-3.5, a branching degree of 30-75 / 1000C, and a crystallinity of 5-30%.

[0054] In a further preferred embodiment, the block polyethylene has a weight average molecular weight of 150,000-350,000 g / mol, a polymer dispersibility index (PDI) of 1.8-3.2, a branching degree of 45-72 / 1000C, and a crystallinity of 7-20%.

[0055] In a preferred embodiment, the melting point T of the block polyethylene is m The melting temperature is 40-100°C, preferably 45-95°C, more preferably 45-90°C, and the melting enthalpy ΔH is 10-70 J / g, preferably 15-65 J / g, more preferably 15-60 J / g.

[0056] In a preferred embodiment, the block polyethylene is prepared by the block polyethylene preparation method of the present application.

[0057] Example

[0058] The embodiments of the present application will be described in detail below in conjunction with examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be construed as limiting the scope of the present application.

[0059] The testing method for the molecular weight of the polymer obtained in the following examples and comparative examples is as follows: The polymer molecular weight is measured using a PL-220 gel permeation chromatograph of Polymer Laboratories, using 1,2,4-trichlorobenzene as the mobile phase, polystyrene as the standard sample, a differential detector, a flow rate of 1.0 mL / min, a measuring temperature of 150° C., and a sample concentration of 2.0 mg / mL. The polymer dispersity index (PDI) is calculated based on the measured weight average molecular weight and number average molecular weight.

[0060] The degree of branching of the polymers obtained in the following examples and comparative examples was calculated based on the carbon nuclear magnetic resonance spectrum. The specific method is as follows: the microstructure of the polyethylene sample was determined using a Bruker Avance 600M nuclear magnetic resonance spectrometer. The sample was dissolved in deuterated o-dichlorobenzene to prepare a solution. The test temperature was 120°C. The nuclear magnetic resonance hydrogen spectrum was obtained by scanning 2000 times and 6000 times respectively. 1 H-NMR) and carbon nuclear magnetic resonance spectroscopy ( 13 C-NMR).

[0061] The thermal properties (melting point T m, melting enthalpy ΔH and crystallinity) testing method is: using TA-2000 differential scanning calorimeter (DSC) to measure, using nitrogen atmosphere, heating from 20°C to 150°C at a rate of 20°C / min, staying for 5 minutes to eliminate thermal history, then decreasing to -70°C at a rate of 20°C / min, staying for 5 minutes, and then increasing to 150°C at a rate of 20°C / min, recording the secondary heating curve.

[0062] The tensile properties (tensile strength and breaking strain) of the polymers obtained in the following examples and comparative examples are tested as follows: the standard GB / T1040-1992 is used for determination, the testing instrument is a universal material testing machine - Zwick / Roell-Z020, the spline type is Type I, and the splines are prepared using a micro high-performance composite material molding system of model HAAKE MiniJet II and a Tensile bar ISO527-5A tensile mold (L75mm, W12.5mm, H2mm), the injection molding temperature is 280-300°C, the mold temperature is 80-100°C, the holding pressure is 1150bar, and the holding time is 15s.

[0063] In the following examples and comparative examples:

[0064] The polymerization activity was calculated as follows:

[0065] W=Q / (M×H)

[0066] Wherein, W is the polymerization activity; Q is the yield of the obtained polymer (in g); M is the total molar amount of catalyst A and catalyst B (in mol); and H is the polymerization time (in h).

[0067] The relative crystallinity X of the polymer is calculated as follows:

[0068]

[0069] ΔH f is the measured melting enthalpy of polyethylene; The melting enthalpy of 100% crystalline polyethylene is 291.7 J / g.

[0070] Example 1

[0071] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B1 (ethylenebis-1,1-(tetrahydroindenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization autoclave with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the autoclave in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P1 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0072]

[0073] Example 2

[0074] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B2 (rac-vinyl bis-indenyl zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P2 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0075] Example 3

[0076] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P3 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0077] Example 4

[0078] In a glove box, the above-mentioned catalyst A4 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P4 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0079]

[0080] Example 5

[0081] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 4.4 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P5 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0082] Example 6

[0083] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization autoclave with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the autoclave in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 11 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P6 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0084] Example 7

[0085] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 80°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P7 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0086] Example 8

[0087] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), triphenyl carbon tetrakis (pentafluorophenyl) borate (0.044 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P8 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0088] Example 9

[0089] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate (0.044 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization autoclave with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the autoclave in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P9 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0090] Example 10

[0091] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization autoclave with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and ethylaluminum dichloride hexane solution (1.0M, 11 mL) were added to the autoclave in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P10 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0092] Embodiment 11

[0093] In a glove box, the above-mentioned catalyst A2 (0.0055 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.0165 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P11 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0094] Example 12

[0095] In a glove box, the above-mentioned catalyst A2 (0.0165 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.0055 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P12 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0096] Example 13

[0097] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and di-n-hexylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer, which was filtered, washed, and then vacuum dried at 60° C. to a constant weight, and the obtained polymer P13 was weighed. The polymerization activity and polymer test results of this example are shown in Table 1.

[0098] Comparative Example 1

[0099] In a glove box, the above-mentioned catalyst A2 (0.011 mmol), catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.011 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution was added to the reactor. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P14 was weighed. The polymerization activity and polymer test results of this comparative example are shown in Table 1.

[0100] Comparative Example 2

[0101] In a glove box, the above-mentioned catalyst A2 (0.022mmol), dichloromethane (10mL), and methylaluminoxane (22mmol) were added to a 100mL conical flask in sequence, mixed and set aside. After purging 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11mL) were added to the kettle in sequence, stirred for 10 minutes, and the above-mentioned catalyst solution and diethylzinc hexane solution (1.0M, 6.6mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5MPa ethylene was introduced, and the polymerization reaction was stirred at 200rpm for 30min. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried to constant weight at 60°C, and the obtained polymer P15 was weighed. The polymerization activity and polymer test results of this comparative example are shown in Table 1.

[0102] Comparative Example 3

[0103] In a glove box, catalyst B3 (dimethylsilyl-bis-(1-indenyl) zirconium dichloride) (0.022 mmol), dichloromethane (10 mL), and methylaluminoxane (22 mmol) were added to a 100 mL conical flask in sequence, mixed, and set aside. After purging a 2L high-pressure polymerization kettle with high-purity nitrogen at 100°C for 2 hours, hexane (1L) and triisobutylaluminum hexane solution (1.0M, 11 mL) were added to the kettle in sequence. After stirring for 10 minutes, the above-prepared catalyst solution and diethylzinc hexane solution (1.0M, 6.6 mL) were added to the reactor in sequence. When the reactor was heated to 60°C, 1.5 MPa of ethylene was introduced, and the polymerization reaction was carried out for 30 minutes at a speed of 200 rpm. After the reaction was completed, the polymerization solution was poured into an acidified ethanol solution to precipitate a solid polymer. After filtering and washing, the polymer was vacuum dried at 60°C to constant weight, and the obtained polymer P16 was weighed. The polymerization activity and polymer test results of this comparative example are shown in Table 1.

[0104] Table 1 Polymerization test results of various embodiments and comparative examples

[0105]

[0106] From the comparison between the above embodiments and the comparative examples, it can be seen that by using the preparation method of the present application, the prepared block polyethylene has a narrower molecular weight distribution, higher tensile strength and elongation at break, thereby giving the polyethylene material a wider application.

[0107] Although the specific implementations of the present application have been described in detail above in conjunction with the embodiments, it should be pointed out that the protection scope of the present application is not limited by these specific implementations, but is determined by the appended claims. Those skilled in the art may make appropriate changes to these implementations without departing from the technical ideas and purposes of the present application, and these changed implementations are obviously also included in the protection scope of the present application.

Claims

1. A method for preparing block polyethylene, comprising the steps of using ethylene as the only polymerization monomer to carry out ethylene solution polymerization in a reaction system to which an α-diimine nickel metal complex, a metallocene complex, a cocatalyst, an alkyl zinc chain shuttling agent and an organic solvent are added, wherein the cocatalyst is selected from at least one of alkyl aluminum, alkyl aluminoxane, halogenated alkyl aluminum, aryl borane and aryl borate.

2. The preparation method according to claim 1, wherein The α-diimine nickel metal complex is selected from one or more metal complexes represented by general formula (Ia) or (Ib): In formula (Ia) and (Ib), R1 and R2 are independently hydrogen, C1-C4 alkyl, C1-C4 haloalkyl, halogen or C1-C4 alkoxy; n is an integer from 0 to 4; R3, R4, R6 and R7 are independently C1-C6 chain alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl or C1-C4 alkyl substituted with phenyl; R5 and R8 are independently hydrogen, C1-C6 chain alkyl, C3-C6 cycloalkyl, unsubstituted or substituted phenyl, C1-C4 alkyl substituted with phenyl, halogen or C1-C4 alkoxy; each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl, wherein the substituted phenyl has 1 to 5 substituents selected from the group consisting of halogen, C1-C4 alkyl and C1-C4 haloalkyl.

3. The preparation method according to claim 1 or 2, wherein The α-diimine nickel metal complex is selected from one or more complexes having the following chemical formulas: Preferably, it is selected from one or more of the complexes having the following chemical formula:

4. The preparation method according to any one of claims 1 to 3, wherein The metallocene complex is selected from one or more metal complexes represented by general formula (II): In formula (II), R' is a C1-C8 straight or branched alkylene group, a C13-C21 diaryl alkylene group, a C2-C8 dialkylsilylene group or a C12-C20 diaryl silylene group, preferably a C1-C4 straight or branched alkylene group, a C13-C17 diaryl alkylene group, a C2-C4 dialkylsilylene group or a C12-C16 diarylsilylene group, more preferably a methylene group, an ethylene group, an isopropylidene group, a diphenylmethylene group, a dimethylsilylene group or a diphenylsilylene group; Each independently represents an unsubstituted or substituted cyclopentadienyl, fluorenyl or indenyl; M is a Group IVB metal, preferably titanium or zirconium; and each X is independently selected from halogen, C1-C6 alkyl or C2-C6 alkenyl.

5. The preparation method according to any one of claims 1 to 4, wherein: The general structural formula of the co-catalyst alkyl aluminum is shown in formula (IIIa), Al(R)3(IIIa) wherein each group R is independently selected from a C1-C8 alkyl group, preferably selected from a methyl group, an ethyl group, a propyl group, a butyl group and an isobutyl group, and more preferably selected from an ethyl group and an isobutyl group; The general structural formula of the co-catalyst alkylaluminoxane is as shown in formula (IIIb) or (IIIc), wherein each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, more preferably selected from methyl and ethyl, and n is any integer in the range of 1-50, preferably any integer in the range of 10-30; The general structural formula of the co-catalyst alkyl aluminum halide is shown in formula (IIId), Al(R)nX3-n(IIId) wherein each group R is independently selected from C1-C8 alkyl, preferably selected from methyl, ethyl, propyl, butyl and isobutyl, more preferably selected from ethyl and isobutyl, X is halogen, preferably chlorine or bromine, and n is 1 or 2; and The cocatalyst arylborane and aryl borate are selected from triphenylboron, tri(pentafluorophenyl)boron, triphenylcarbon tetra(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(pentafluorophenyl)borate, triethylammonium tetra(pentafluorophenyl)borate, 1-butyl-3-methylimidazole tetrafluoroborate, ferrocene tetrafluoroborate, trimethylammonium tetraphenylborate, triethylammonium tetraphenylborate, triisopropylammonium tetraphenylborate, tri-n-butylammonium tetraphenylborate, trimethylammonium tetra(4-methylphenyl)borate, triisopropylammonium tetra(4-methylphenyl)borate, trimethyl One or more of tris(pentafluorophenyl)boron, triphenylcarbon tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and triethylammonium tetrakis(pentafluorophenyl)borate.

6. The preparation method according to any one of claims 1 to 5, wherein Calculated on the basis of the central metal atom, the molar ratio of the α-diimine nickel metal complex to the metallocene complex added in the reaction system is 1:10 to 10:1, preferably 2:8 to 8:2, and more preferably 4:6 to 6:

4.

7. The preparation method according to any one of claims 1 to 6, wherein: The molar ratio of the total amount of the co-catalyst alkylaluminum, alkylaluminoxane and alkylaluminum halide added to the reaction system, calculated as aluminum atom, to the total amount of the α-diimine nickel metal complex and the metallocene complex, calculated as central metal atom, is (10-5000):1, preferably (100-2000):1, more preferably (500-1000):1; and / or The molar ratio of the total amount of the co-catalyst arylborane and aryl borate added to the reaction system, calculated as boron atoms, to the total amount of the α-diimine nickel metal complex and the metallocene complex, calculated as central metal atoms, is (1-10):1, preferably (2-5):

1.

8. The preparation method according to any one of claims 1 to 7, wherein The alkyl zinc chain shuttling agent is selected from at least one of the organic zinc compounds shown in the general structural formula (IV), Zn(R)2(IV) Wherein, each group R is independently selected from C1-C10 straight chain or branched alkyl, preferably selected from at least one of methyl, ethyl, isopropyl, n-butyl, isobutyl and n-hexyl, more preferably selected from at least one of methyl and ethyl.

9. The preparation method according to any one of claims 1 to 8, wherein The molar ratio of the amount of the alkyl zinc chain shuttling agent added to the reaction system, calculated as zinc atom, to the total amount of the α-diimine nickel metal complex and the metallocene complex, calculated as central metal atom, is (1-1000):1, preferably (50-600):1, and more preferably (100-500):

1.

10. The preparation method according to any one of claims 1 to 9, wherein the organic solvent is selected from aromatic hydrocarbons, alkanes and halogenated alkanes, preferably selected from one or more of toluene, dichloromethane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane and Isopare series solvents, more preferably selected from one or more of n-pentane, n-hexane, cyclohexane, toluene and dichloromethane.

11. The preparation method according to any one of claims 1 to 10, wherein the conditions of the polymerization reaction include: The temperature is 0-150°C, preferably 60-100°C; the polymerization pressure is 0.1-4.0 MPa, preferably 0.5-3.0 MPa.

12. A block polyethylene having a weight average molecular weight of 50,000-1,000,000 g / mol, preferably 100,000-400,000 g / mol, more preferably 150,000-350,000 g / mol, a polymer dispersibility index (PDI) of 1.5-4.0, preferably 1.6-3.5, more preferably 1.8-3.2, a degree of branching of 20-75 / 1000C, preferably 30-75 / 1000C, more preferably 45-72 / 1000C, and a degree of crystallinity of 5-35%, preferably 5-30%, more preferably 7-20%.

13. The block polyethylene according to claim 12, having a melting point T m The melting enthalpy ΔH is 10-70 J / g, preferably 15-65 J / g, more preferably 15-60 J / g. Preferably, the block polyethylene is prepared by the preparation method according to any one of claims 1-11.

Citation Information

Patent Citations

  • Multi-block branched polyethylene and preparation method thereof

    CN106589181A

  • Composite catalyst and application thereof

    CN114853947A

  • Acenaphthyl alpha-diimine nickel complex, catalyst and application of acenaphthyl alpha-diimine nickel complex

    CN116462715A

  • Polymerization catalyst system and polymerization process

    US6291608B1